The role of expression in the emergence of cultural forms and symbolic types - Dacrotsis, Dimitrios (Epistēmēs Metron Logos, 2023)
This study explores the correlation between historical events and their emergence as singular expressions of a society or culture. When reliable sources permit an understanding of such moments as manifestations of universal volitions—namely, moral will—they offer a framework for interpreting both the modalities of their emergence and their relation to historical phenomena. The analysis focuses on cultural forms and symbolic types, examined as constituent elements within broader cultural systems. Simultaneously, attention is directed toward the symbolic environments in which these forms were constituted and through which they emerged. These environments will be approached through the epistemic categories of theoretical and practical knowledge. Particular emphasis will be placed on the role of aesthetic supervision as the primary level of theoretical cognition, preceding logical operations and intersecting with practical reason, individual volition, and ethical orientation.